Does Firm’s ESG performance matters for corporate export? Evidence from China - Yang, Qihan (Transactions on Economics, Business and Management Research, 2024)
Firms' ESG performance is a vital factor for sustainable development. Corporate export, as one of the most significant firm international strategies, plays a crucial role in their decision-making. This study conducts theoretical analysis and empirical tests on the relationship between firm’s ESG performance and corporate export using panel data of Chinese listed companies from 2011 to 2016. We employ the fixed effect regression model based on the panel dataset and find that firm’s ESG performance significantly positively affects corporate export. Our main findings have certain implications for enterprises in coping with sustainable development and empowering the international corporate strategy.